Prevalence of use of on-label and off-label psychotropics in the Greek pediatric population - Pesiou, Stella; Barcelo, Rafel; Papazisis, Georgios; Torres, Ferran; Pontes, Caridad (Frontiers in Pharmacology, 2024)
With a global increased use of psychotropics in pediatrics, their off-label use is a concern due to uncertainty and risk. Data on psychotropics use in the Greek pediatric population do not exist to date.We analyzed retrospective data from the nationwide pharmacy claim database, to estimate the prevalence of psychotropics in pediatrics focusing on off-label use (March 2016-October 2019). In total 63,782 pediatric subjects had at least one identified psychotropic prescription. The prevalence of psychotropics use was 5.1-14.6/1,000 pediatric inhabitants. When excluding 42,508 subjects who received only short-time hydroxyzine, the prevalence was 3.1-6.5/1,000 pediatric inhabitants; adolescents and boys had higher exposures. An in-depth analysis of 21,274 subjects accounting for 222,307 psychotropic dispensations, showed antiepileptics as the most frequent psychotropics, consistently with the finding on epilepsy being the most frequent diagnosis; diazepam was the single drug with the highest exposure in almost all ages. 14% of subjects have received at least one medicine with no pediatric information in the labelling, corresponding to 5.5% of dispensed psychotropics. 7.6% of all dispensed psychotropics were used in a non-authorized age range with quetiapine being the most frequent psychotropic as off-label age range; antipsychotics and antidepressants were first as off-label for non-authorized indication.Data from Greece show that a relevant number of patients are prescribed psychotropics, with 1 in 7 being under off-label use. Due to the limitations inherent to pharmacy claims databases, further research using clinical data for a longer follow-up period could confirm and identify trends in psychotropics use in Greece.